The Role of PAI Teachers on the Level of Awareness of Congregational Prayer Among Grade XI Students of Phase F SMKN 2 Bukittinggi - Arif Saputra; Halomoan, Halomoan (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
Prayer is the second pillar of Islam and is obligatory for every accountable Muslim. However, many students are negligent or even abandon their prayers, especially congregational prayers. This study aims to analyze the role of Islamic Religious Education (IRE) teachers in increasing the awareness of congregational prayer among Grade XI Phase F students at Public vocational secondary schools 2 Bukittinggi. This research uses a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results show that IRE teachers play a significant role in enhancing students’ awareness of congregational prayer by acting as role models, instilling habits, giving attention, and providing advice. The teacher's role has a meaningful connection with students’ motivation to perform congregational prayers regularly. Through the active role of IRE teachers, students' spiritual awareness can be fostered effectively within the school environment